PENGARUH PERBEDAAN KEMATANGAN AIR KELAPA HIJAU SEBAGAI BAHAN PENGENCER YANG DITAMBAH 10% KUNING TELUR TERHADAP KUALITAS SEMEN CAIR KAMBING BOER - Rara Putri Audia; Muhammad Ade Salim; Nurul Isnaini; Trinil Susilawati (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
This study is conducted on December 2016until January 2017 in Sumber Sekar Field Laboratory, Faculty of Animal Husbandry, Brawijaya University. The purpose of this study is to determine the effect of different maturity levels of green coconut water dilution with 10% of egg yolk to the sperm quality of Boer goat during storage. Materials used in the study were male Boer kept in Sumber Sekar Field Laboratory. The semen was collected routinely once in 2 days using artificial vagina with fresh semen quality requirement individual motility ≥70%. The method used in this study is Randomnized Block Design which consists of three treatments, there are P0 as control (CEP-2 + 10% Egg Yolk); P1 (Young Green Coconut Water + 10% Egg Yolk) and P2 (Mature Green Coconut Water + 10% Egg Yolk). If the difference between the treatments showed real influence, then the Duncan’s Multiple Range Test will be done. The grouping is sorted by the semen observation time. The observed variables macroscopically include volume, smell, consistency, color and acidity, and microscopically which include individual motility, mass motility, viability and abnormality.The study result for the mean and standard deviation (SD) of motility in storage until the 4th day. The motility of P0 (36.67 ± 32.96)%, then P1 (20.0 ± 13.78)%, and the last P3 (18.33 ± 19.15). Dilution with the best viabillity average in the 4th day in P0 (58.02 ± 19.93)%, in P1 (26.10 ± 18.47)% and the last is P2 (25,87 ± 20,60)%.the average value of abnormality on the 4th day shows that the lowest average abnormality found in P0 (1.49 ± 0.73)%, then P1 (1.89 ± 1.68)% and the highest average value of abnormality is in P2 (2,87 ± 1.41).Keywords : liquid semen, boer goat, green coconut water, CEP-2, cold storage